“I am happy to be alive, but I prefer to have children without my chronic disease”: chronically ill persons’ views on reproduction and genetic testing for their own condition - Anika König; Stefan Reinsch (New Genetics and Society)
In Germany, the debate on preimplantation and prenatal testing is heavily influenced by the idea of an antagonism between prospective parents and their potential children. Underlying this antagonism is the assumption that prospective parents follow an ableist logic and do not regard the lives of children with a chronic illness as “worth living”. Taking the example of two rare genetic illnesses, Marfan Syndrome and Cystic Fibrosis, we investigate how persons who themselves are affected by these conditions view preimplantation or prenatal testing for their condition in the context of reproductive decision-making. Our empirical research shows that chronically ill patients’ appreciation of their own life as a “life worth living” does not always translate into an unequivocal wish and readiness to give birth to a child that is affected by their condition as well and argue that taking their views into consideration adds an additional level of complexity to the debate.